a) ( x – 1 ) ( x + 2 ) +5x = x^2 + 4 b) x( x + 5 ) – 4x – 20 = 0

a) ( x – 1 ) ( x + 2 ) +5x = x^2 + 4
b) x( x + 5 ) – 4x – 20 = 0

0 thoughts on “a) ( x – 1 ) ( x + 2 ) +5x = x^2 + 4 b) x( x + 5 ) – 4x – 20 = 0”

  1. `a, (x-1)(x+2)+5x=x^2+4`

    `→x^2+x-2+5x=x^2+4`

    `↔x-6+5x=0`

    `↔6x=6`

    `↔x=1`

    Vậy `x=1`

    `b, x(x+5)-4x-20=0`

    `↔x^2+5x-4x-20=0`

    `↔x(x+5)-4(x+5)=0`

    `↔(x-4)(x+5)=0`

    `↔x=4` hoặc `x=-5`

    Vậy `x=4` hoặc `x=5`

    Reply
  2. Đáp án:

     a) Ta có: ( x – 1 ) ( x + 2 ) +5x = x² + 4

    ⇒   x² – x + 2x – 2 + 5x            =x² + 4

    ⇒        x² – x² – x + 2x + 5x     =4 + 2

    ⇒                         6x                 =6

    ⇒                                   x         =1

                Vậy x=1

    b) x( x + 5 ) – 4x – 20 = 0

    ⇒        x(x+5)-4(x+5) =0

    ⇒          (x-4)(x+5)      =0

          x-4=0⇒x=4

    ⇒hoặc

          x+5=0⇒x=-5

      Vậy x=4 hoặc x=-5

     XIN TLHN VÀ 5* NHÉ

     

    Reply

Leave a Comment